Absolute Poverty of Early Childhood Children: A Comparative Analysis of Java and Non-Java - Lucie Suparintina; Bambang Eko Afiatno (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2020)
The development of quality human resources in the future depends on the development of children today. Deprived children's basic needs, such as preschool education, protection, health, and nutrition, make it difficult for children to be free from poverty. This study aims to analyze the determinants of early childhood children aged 3-6 years old who suffer from absolute poverty in Java, Bali-Nusa Tenggara, and Maluku-Papua using logistic regression. The results showed that the majority of early childhood children in Java deprive in 1 dimension. However, in the other regions, the majority of them are deprived in 2 dimensions. The education level of both the household head and the mother and the residential area had a significant effect on the possibility of an absolute poverty early childhood children in all regions. Government programs such as 12-year required education, agricultural business capital, and infrastructure development in rural areas need to be improved further.JEL Classification: I15, I25, I32How to Cite:Suparintina, L., & Afiatno, B. E. (2020). Absolute Poverty of Early Childhood Children: a Comparative Analysis of Java and Non-Java. Signifikan: Jurnal Ilmu Ekonomi, Vol. 9(1), 107-122. doi: http://dx.doi.org/10.15408/sjie.v9i1.14056.